Biomechanical and physiological response to a contemporary soccer match-play simulation - Page, R. M.; Marrin, K.; Brogden, C. M.; Greig, M. (The Journal of Strength and Conditioning Research, 2015)
The intermittent activity profile of soccer match play increases the complexity of the physical demands. Laboratory models of soccer match play have value in controlled intervention studies, developed around manipulations of the activity profile to elicit a desired physiological or biomechanical response. Contemporary notational analyses suggest a profile comprising clusters of repeat sprint efforts, with implications for both biomechanical and physiological load. Eighteen male soccer players completed a 90-minute treadmill protocol based on clusters of repeat sprint efforts. Each 15-minute bout of exercise was quantified for uniaxial (medial-lateral [PLML], anterior-posterior [PLAP], and vertical [PLV]) and triaxial PlayerLoad (PLTotal). The relative contributions of the uniaxial PlayerLoad vectors (PLML%, PLAP%, and PLV%) were also examined. In addition to rating of perceived exertion, the physiological response comprised heart rate, blood lactate concentration, and both peak and average oxygen consumption. Triaxial PlayerLoad increased (p = 0.02) with exercise duration (T0-15 = 206.26 ± 14.37 a.u. and T45-60 = 214.51 ± 14.97 a.u.) and remained elevated throughout the second half. This fatigue effect was evident in both the PLML and PLAP movement planes. The mean relative contributions of PLV%:PLAP%:PLML% were consistent at ~48:28:23. The physiological response was comparable with match play, and a similar magnitude of increase at ~5% was observed in physiological parameters. Changes in PlayerLoad might reflect a change in movement quality with fatigue, with implications for both performance and injury risk, reflecting observations of match play. The high frequency of speed change elicits a 23% contribution from mediolateral load, negating the criticism of treadmill protocols as "linear."